2016
DOI: 10.1002/pssb.201600092
|View full text |Cite
|
Sign up to set email alerts
|

Negative linear compressibility from rotating rigid units

Abstract: The possibility of achieving the anomalous property of negative linear compressibility through a mechanism involving the rotations of rigid units is presented and discussed through analytical modelling. It is shown that some rotating rigid units with particular geometric features and connectivities will expand rather than contract in certain directions when a hydrostatic pressure is applied. The conditions required for this anomalous property to be achieved via rotations are elucidated in terms of specific geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 78 publications
2
31
0
Order By: Relevance
“…And the expressions of Poisson's ratios of these two models are same due to the same framework structure so the euqation, β L (OX i ) (Model I) = 2 β L (OX i ) (Model III) , can be easily to understand. More than that, through the comparison of these two models, it can be indicated that in addition to the geometry features which have already been widely discussed , the arrangement of the framework structure can also have a great effect on the compressibility properties and arranging the framework in a dense way just like the Model III is not conductive to the enhancement of negative compressibility effect.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…And the expressions of Poisson's ratios of these two models are same due to the same framework structure so the euqation, β L (OX i ) (Model I) = 2 β L (OX i ) (Model III) , can be easily to understand. More than that, through the comparison of these two models, it can be indicated that in addition to the geometry features which have already been widely discussed , the arrangement of the framework structure can also have a great effect on the compressibility properties and arranging the framework in a dense way just like the Model III is not conductive to the enhancement of negative compressibility effect.…”
Section: Discussionmentioning
confidence: 96%
“…And the expressions of Poisson's ratios of these two models are same due to the same framework structure so the euqation, β L (OX i ) (Model I) ¼ 2β L (OXi ) (Model III) , can be easily to understand. More than that, through the comparison of these two models, it can be indicated that in addition to the geometry features which have already been widely discussed [10][11][12][13][14][15][16] , the arrangement of the framework structure can also have a great effect on the compressibility properties and arranging the framework in a dense way just like the Model III is not conductive to the enhancement of negative compressibility effect. Before comparing the compressibility properties of the Models I and II, we need to analyze the compressibility properties of the hinging hexagonal truss mechanism, which is helpful to understand the differences of the linear compressibility properties between these two models.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations